Patients' and providers' evaluations of telepsychiatry and future directions: A literature review of mixed research methods - Ikuko Natsukari; Norio Ozaki (PCN Reports)
Abstract Regarding the use of telemedicine after the COVID‐19 pandemic, there has been little consideration of the patient's perspective. In this review, we aimed to examine the future direction of telemedicine by reviewing the literature that evaluated telemedicine from a patient‐centered perspective and providers' perspective using a mixed research method. A search of studies containing keywords related to “telemedicine,” “patient satisfaction,” and “patient perspective” was conducted using MEDLINE from January 2014 to August 2024. The study was conducted using a mixed research method. Eleven articles were extracted, including studies that used combined evaluation by healthcare providers. The method of integration of quantitative and qualitative studies included eight convergent designs and three explanatory sequential designs. In quantitative surveys, patients' evaluations of telepsychiatry were generally favorable, with the main advantages being convenience and access. In qualitative surveys, heterogeneity in results was observed depending on patients' conditions and social factors, such as the presence of chronic diseases and stigma, while difficulties in symptom assessment were cited by healthcare providers. The continuation of telepsychiatry after a pandemic requires collecting detailed opinions of patients using mixed research methods, qualitative surveys, and evaluation and improvement through controlled studies and studies using large, diverse samples.